Effects of stepwise changes in dissolved carbon dioxide concentrations on metabolic activity in Chlorella for spaceflight applications. (May 2021) - Matula, Emily E.; Nabity, James A.
Abstract: This paper assesses the impacts to the growth rate, health, oxygen production, and carbon dioxide fixation and nitrogen assimilation of Chlorella vulgaris while sparging the culture with various influent concentrations of carbon dioxide. Selected concentrations reflect a cabin environment with one crew member (0.12% v/v) and four crew members (0.45% v/v). Stepwise, sustained changes in influent carbon dioxide concentration on day four of the eight-day experiments simulated a dynamic crew size, reflective of a planetary surface mission. Control experiments used constant influent concentrations across eight days. Significant changes in growth rate (0.12%-to-0.45%: 57% increase; 0.45%-to-0.12%: 59% reduction) suggest a positive correlation between metabolic activity of C. vulgaris and environmental carbon dioxide concentration. Statistical tests illustrate that algae are more sensitive to reductions in influent carbon dioxide. No specific correlation of the nitrogen assimilation rate to influent carbon dioxide, suggesting a nitrogen-limited or irradiance-limited system. Photosynthetic yield results (0.59–0.72) indicate that the culture was minimally stressed in all tested conditions. This paper compares these results to findings of published, steady-state experiments conducted under similar carbon dioxide environments. The findings presented here imply that a sufficient volume of C. vulgaris, with nutrient supplementation or biomass harvesting, could support the respiratory requirements of a long duration human mission with a dynamic cabin environment and these data can be used in future dynamic models.